CEO Compensation and Earnings Management - Zhang, Jun (2017)
This paper examines the effects of CEO compensation package on earnings quality. I find that the proportions of restricted stocks and stock options in CEO compensation are significantly and negatively related to earnings quality. I do not find any evidence that salary and bonus payments have significant effect on earnings quality. My research results also indicate that firm size, Z-score, ROA all have significant relationships with earnings quality. Larger firm size and Z-score will decrease earnings quality, while higher ROA will increase earnings quality.